باللغة الانجليزيةAdvertisingمقياس الاشهار - سلامي اسعيداني (جامعة محمد بوضياف -المسيلة, 2025)
Advertising -Summary: Teaching advertising at the university level has great importance and influence on many public areas, and this importance is summarized in the following axes: • Teaching the subject helps build credibility in the work environment, especially when companies respect customers and provide a set of correct information about the nature of the product that was advertised. It contributes to using an efficient and effective strategy that clarifies the costs incurred by the products that may be included in advertising, especially with private commercial advertisements in production and service companies. • Teaching students to create advertisements capable of attracting many customers; the more distinctive the advertising style is, the more it contributes to achieving the desired impact on the targeted customer group in society. • Supporting the communication of ideas to students from types of advertising by using the method of repeated advertisements that depend on an appropriate advertising policy, such as advertisements within news bulletins, or television series. • Linking advertisements with search engines and websites on the Internet, which helps in enhancing the role of advertising in communicating the advertising idea to individuals, specifically those who browse the Internet constantly